Small molecule angiotensin converting enzyme inhibitors: A medicinal chemistry perspective - Wenyue Zheng; Wenyue Zheng; Erkang Tian; Zhen Liu; Changhan Zhou; Pei Yang; Pei Yang; Keyue Tian; Wen Liao; Juan Li; Changyu Ren (Frontiers Media S.A., 2022)
Angiotensin-converting enzyme (ACE), a zinc metalloprotein, is a central component of the renin-angiotensin system (RAS). It degrades bradykinin and other vasoactive peptides. Angiotensin-converting-enzyme inhibitors (ACE inhibitors, ACEIs) decrease the formation of angiotensin II and increase the level of bradykinin, thus relaxing blood vessels as well as reducing blood volume, lowering blood pressure and reducing oxygen consumption by the heart, which can be used to prevent and treat cardiovascular diseases and kidney diseases. Nevertheless, ACEIs are associated with a range of adverse effects such as renal insufficiency, which limits their use. In recent years, researchers have attempted to reduce the adverse effects of ACEIs by improving the selectivity of ACEIs for structural domains based on conformational relationships, and have developed a series of novel ACEIs. In this review, we have summarized the research advances of ACE inhibitors, focusing on the development sources, design strategies and analysis of structure-activity relationships and the biological activities of ACE inhibitors.